METODE TALKING STICK PENERAPAN METODE TALKING STICK DENGAN MEDIA VIDEO PEMBELAJARAN UNTUK MENINGKATKAN KREATIVITAS DAN PRESTASI BELAJAR PENDIDIKAN AGAMA HINDU DAN BUDI PEKERTI KELAS VIII SMP MUTIARA SINGARAJA: Talking Stick Method, Learning Creativity, Academic Achievement, Hindu Religious and Character Education - Putu Chandra Caka Narayani; I Wayan Suwendra; Komang Tari Karismayanti (Jurnal Widya Sastra Pendidikan Agama Hindu, 2025)
This study aims to determine the effectiveness of the application of the Talking Stick method with learning video media to increase the creativity and learning achievement of grade VIII students of Mutiara Singaraja Junior High School in the subject of Hindu Religious Education and Ethics for the 2024/2025 Academic Year. The Talking Stick method provides space for students to participate in the learning process by taking turns using a stick when expressing opinions or answering questions. This technique fosters confidence, as well as the ability to work between students. The use of learning video media as a tool to display material audio-visually that can help students understand thoroughly and is fun. The combination of the Talking Stick method and learning videos is able to create a learning environment that encourages more comprehensive student engagement, which has an impact on increased creativity and learning achievement. This research uses a Classroom Action Research (PTK) approach which is carried out in two cycles. Each cycle consists of the stages of planning, implementation of actions, observation, and reflection. The subjects of this study were 31 grade VIII students. The results of the study showed a significant improvement. Students' creativity increased from 65.87% in the pre-action, then increased in the first cycle to 71.6% but it was not achieved in the first cycle, so the research continued to the second cycle and obtained a creativity result of 84.8%. The average learning achievement score increased from 61.7 with 61.7% absorption and classical completeness of 29% in pre-action, to 76.4 with 76.4% absorption and 41.93% learning completeness in the first cycle, and in the second cycle there was an increase where the average score was 84.81 with 84.81% absorption and learning completeness was 90.3%. Thus, this method has been proven to be effective in increasing student participation, creativity, and learning achievement.